Clinical and Microbiological Characteristics of Colistin-Resistant Enterobacteriaceae at a Large Tertiary Care Center in Michigan. (4th October 2017) - Mills, John P; Henig, Oryan; Patel, Twisha; Washer, Laraine L; Bachman, Michael A; Dombecki, Carey; Kaye, Keith S
Abstract: Background: Plasmid-mediated colistin resistance ( mcr -1) has raised concerns regarding widespread dissemination of polymyxin resistance. The epidemiology of colistin resistance among Enterobacteriaceae was evaluated at Michigan Medicine. Methods: Data pertaining to patients who had clinical Enterobacteriaceae isolates with a colistin MIC ≥ 4 µg/L between 1/2016 and 3/2017 were collected. All clinical isolates of Enterobacteriaceae were routinely tested for colistin susceptibility by broth microdilution (TREK Sensititre) during the study period. Prior healthcare exposure was defined as a stay for ≥ 48 hours in a hospital or long-term care facility within 90 days prior to culture. Antibiotic exposure was captured for 90 days prior to culture. Select isolates were tested for the mcr -1 gene by PCR. Results: Of 15, 894 isolates tested, 120 (0.75%) from 98 unique patients had a colistin MIC ≥ 4 µg/L. Thirteen patients were excluded due to lack of clinical data. Of the remaining 85 cases, > 70% were community-acquired and > 40% had prior healthcare exposure (table). Most isolates were urinary. Sixty percent of cases had prior antibiotic exposure. Multidrug resistance was uncommon. Of 23 unique patient isolates tested, 3 (13%) were mcr -1 positive, and all were E. coli . Conclusion: The majority of patients acquired colistin-resistant Enterobacteriaceae in the community. Isolates were susceptible to most non-polymyxin antibiotics. mcr -1 was detected in 3 isolates. Disclosures: T. Patel, Merck: Grant Investigator, Research grant. K. S. Kaye, Xellia: Consultant, Consulting fee. Merck: Consultant and Grant Investigator, Consulting fee and Research support. The Medicines Company: Consultant and Grant Investigator, Consulting fee and Research support